Treatment of bleeding episodes with recombinant factor VIII Fc fusion protein in A‐LONG study subjects with severe haemophilia A. Issue 3 (20th February 2017) - Shapiro, A. D.; Mahlangu, J. N.; Perry, D.; Pasi, J.; Quon, D. V.; Chowdary, P.; Tsao, E.; Li, S.; Innes, A.; Pierce, G. F.; Allen, G. A.
Abstract : Introduction: The Phase 3 A‐LONG study demonstrated the safety and efficacy of rFVIIIFc for the control and prevention of bleeding episodes in severe haemophilia A. Aim: To describe the treatment of bleeding episodes with rFVIIIFc in the A‐LONG study. Methods: A‐LONG subjects (<1 IU dL −1 endogenous FVIII) were treated with individualized prophylaxis (Arm 1), weekly prophylaxis (Arm 2) or episodic treatment (Arm 3). Information recorded for each bleeding episode included type, location and dose to treat the episode. Results: During A‐LONG, 757 bleeding episodes occurred during the efficacy period; the majority [456 (60%)] occurred in Arm 3 (episodic treatment). Of 93 subjects in the prophylaxis arms who entered the study with target joints, 43 (60%) in Arm 1 and 11 (52%) in Arm 2 did not experience a target joint bleed. Overall, 98% of bleeding episodes (and 98% of bleeds involving a target joint) resolved with one or two infusions; the median dose per infusion to treat a bleed was 27 IU kg −1 (27 IU kg −1 for target joints). Using population pharmacokinetic simulations, FVIII activity levels were predicted to be below the upper limit of normal (150 IU dL −1 ) in most patients in the event that rFVIIIFc is used to treat a bleeding episode in close proximity to a prophylactic dose. Conclusions: These findings demonstrate the efficacy of rFVIIIFc for the treatment of acute bleeding episodes in subjects with severe haemophilia A, regardless of treatment regimen.